Craniosynostosis in a South Africa population - Crous, Ilse (Division of Human Genetics, 2021)
Background: Craniosynostosis refers to the premature fusion of calvarial bones which lead to restricted growth potential. Compensatory growth occurs in the dimensions not restricted by fusion and causes progressive distortion in the skull shape. The majority of craniosynostosis cases occur in isolation and are so called non-syndromic craniosynostosis. In about 30 % of all cases, anomalies are noted along with the craniosynostosis, often defining a described and recognised syndrome. The aim is to delineate the phenotype observed in a South African population. Methods: In this descriptive study, hospital records for the preceding five years were retrospectively reviewed to describe the profile of patients with craniosynostosis seen at the Red Cross War Memorial Children's Hospital in Cape Town. In addition to the retrospective review, a sub cohort of patients were prospectively phenotyped. The patients were subdivided into three groups namely: non-syndromic craniosynostosis, syndromic craniosynostosis and craniosynostosis with additional features. The last group included patients who had additional malformations or clinical findings without a syndromic diagnosis. The prevalence of phenotypic findings, teratogen exposure, birth complications, congenital malformations, surgical interventions and results of genetic testing in this cohort is described. Descriptive statistical analysis was used. Results: A total of 47 children with craniosynostosis were included in this study. Twenty-five individuals of the cohort were male, and one patient has a disorder of sexual development. Eighteen patients had non-syndromic synostosis. Twelve of these had sagittal type synostosis and five had metopic type synostosis with one unspecified. Thirteen had syndromic synostosis. Eight were clinically diagnosed with Crouzon syndrome of which three were molecularly confirmed. Four patients had Apert syndrome and one had Pfeiffer syndrome, these were clinically diagnosed without molecular confirmation. Sixteen patients had craniosynostosis with some additional findings but no syndromic diagnosis. The suture involved in the majority of patients was the sagittal suture. Ten patients had an additional structural brain abnormality and 13 had signs of raised intracranial pressure. The average age at confirmation of diagnosis of craniosynostosis by CT scan was 22.5 months (SD = 31.4, range: 0.1 – 140.9). Thirty of the 47 patients had craniosynostosis surgery. The average age of surgery was 22.4 months (SD = 19; range: 5-79). The anthropometric, phenotype and developmental features indicate that this is a highly heterogenous group of disorders. Conclusion: Craniosynostosis has been widely reported worldwide, especially in individuals of European descent with only a few reports on craniosynostosis in South African or African populations. Knowledge of the phenotypic spectrum will aid in understanding and documenting this group of disorders in our local population. This study also highlights that this is a complex condition best managed by a multidisciplinary team that should include a medical geneticist. The recognition of specific craniosynostosis syndromes together with appropriate molecular testing can be cost effective even in a limited resource setting and aid in accurate prognosis and recurrence risk information for families.